Valoração ecológica de áreas de preservação permanente - Roncon, Thiago Junqueira (2011)
This dissertation uses Emergy Accounting tool, Ecosystem Functional Evaluation and System Ecology approaches to estimate the economic value of Permanent Preservation Areas in São Paulo State, Brazil. Economic values related to natural goods, environmental services and environmental damage were assessed for five case studies located on Serra da Mantiqueira region, which is characterized by semideciduous natural vegetation. This study considered different time period for natural secondary succession: 0, 7, 25, 75 and 200 years. The following natural goods were taking into account for economic valuation: (1) Carbon stock; (2) Decomposers; (3) Nutrients and edaphic structure; (4) Soils and rhizosphere structure; (5) Clay. The economic value in Emdollars (EmUS$) of environmental goods reached 1,180 EmUS$/ha for 0 years time period, 12,922 EmUS$/ha for 7 years, 51,615 EmUS$/ha for 25 years, 182,711 EmUS$/ha for 75 years and 651,520 EmUS$/ha for 200 years. The following environmental services were taking into account for economic valuation: (1) Carbon sequestration and atmosphere chemical composition regulation; (2) Supply of water and soluble minerals to the rivers; (3) Aquifers recharge; (4) Water infiltration; (5 ) Climate regulation; (6) Supplier of food for wild fauna and flora of surrounding ecosystems; (7) Bees pollination, biological control of diseases, increased soil fertility and vegetation productivity of natural ecosystem. The economic value in EmReais (EmR$) of environmental services on natural ecosystem reached 2,181 EmR$/ha.yr for 0 years time period, 4,162 EmR$/ha.yr for 7 years, 4,587 EmR$/ha.yr for 25 years, 4,993 EmR$/ha.yr for 75 years and 4,814 EmR$/ha.yr for 200 years. The x economic value of natural internal areas maintenance were also accounted for: (1) Protection and/or soil formation and soil erosion control; (2) Soil nutrient cycling. These internal services reached 1,257 EmUS$/ha.yr for 0 years, 2,073 EmUS$/ha.yr for 7 years, 2,581 EmUS$/ha.yr for 25 years, 2,984 EmUS$/ha.yr for 75 years and 4,478 EmUS$/ha.yr for 200 years. Finally, the environmental damage identified and evaluated were: (1) Soil erosion processes; (2) Loss of soil structure and edaphic nutrients. Their economic values were 31,832 EmR$/ha.yr for 0 years and 0.0 EmUS$/ha.yr for all other years. All values obtained showed an upward trend according to age of natural secondary succession. Moreover to estimate economic values for environmental services, natural goods and environmental damages, this work shows that the farm s owners whose have natural preserved areas are directly beneficed, as well as society. The indicators obtained in this work highlight the importance of preserved areas with natural vegetation whose economic values should be considered by decision makers for public policies elaboration.